A comparison of inflammatory indicators in twins on the first postnatal day (Annals of Medical Research, 2021)
Aim: To investigate markers of sepsis/inflammation in twin neonates according to placental, demographic, neonatal, and twin-related complications. Materials and Methods: In this retrospective study, we compared these parameters in twins with suspected sepsis for whom laboratory data on infection markers were available on the first postnatal day. Sepsis was later ruled out in all the neonates. After obtaining institutional ethics committee approval, twin pairs who were admitted to the neonatal intensive care unit of Hacettepe University IhsanDogramacı Children's Hospital between 2005 and 2017 were screened for inclusion. Data on the twins’ sepsis markers, complete blood counts, immature to total neutrophil (I/T) ratios, procalcitonin and CRP levels, and blood culture results in the first 24 h of life were recorded.Results: In total, 194 twin pairs (388 neonates) were included in the study. Of the 194 twin pairs, 50 were monochorionic twins (25.8 %), and the remaining 144 (74.2 %) were dichorionic twins. Monochorionic and dichorionic twins, twin-to-twin transfusion syndrome with twins and discordant twins showed no significant differences in I/T ratio, procalcitonin, or CRP values in the first 24 h (p>0.05).Conclusion: Based on our findings, chorionicity (monochorionic/dichorionic placenta), twin-to-twin transfusion syndrome, and size discordance were not related to any significant differences in the CRP level, procalcitonin level, or I/T ratio.